An effective method and model: For optimizing production taking into account environmental - A., Kadyrbergenova; K., Orazbayeva; B., Utenova; M., Kulubekov; L., Kurmangaziyeva (International Journal of Innovative Research and Scientific Studies, 2025)
The proposed model includes in the optimization criterion, in addition to income, the possible payment in case of exceeding pollution norms, which stimulates production to introduce cleaner, environmentally friendly technology. The problems are often difficult to formalize and are characterized by vagueness of initial information, which requires the formulation of multi-criteria production optimization problems taking into account environmental standards in a fuzzy environment and the development of methods for their solution. The aim of the research is to create a model of production optimization taking into account environmental standards, to formulate and solve a multi-criteria optimization problem in a fuzzy environment, and to develop a heuristic method. In this paper, based on the modification of the principles of the main criterion, Pareto optimality, the formulation of a multi-criteria optimization problem considering environmental constraints is obtained, and a heuristic method of its solution is proposed for effective resolution in a fuzzy environment. The originality of the proposed method is that it allows obtaining an adequate solution in a fuzzy environment by maximizing the use of fuzzy information, knowledge, experience, and intuition of the decision maker and experts. A new model for optimizing production is proposed, which is applicable in the field of macroeconomics and microeconomics.